β-Amyloid Clustering around ASC Fibrils Boosts Its Toxicity in Microglia - Lea L. Friker; Hannah Scheiblich; Inga V. Hochheiser; Rebecca Brinkschulte; Dietmar Riedel; Eicke Latz; Matthias Geyer; Michael T. Heneka (Cell Reports, 2020)
Summary: Alzheimer’s disease is the world’s most common neurodegenerative disorder. It is associated with neuroinflammation involving activation of microglia by β-amyloid (Aβ) deposits. Based on previous studies showing apoptosis-associated speck-like protein containing a CARD (ASC) binding and cross-seeding extracellular Aβ, we investigate the propagation of ASC between primary microglia and the effects of ASC-Aβ composites on microglial inflammasomes and function. Indeed, ASC released by a pyroptotic cell can be functionally built into the neighboring microglia NOD-like receptor protein (NLRP3) inflammasome. Compared with protein-only application, exposure to ASC-Aβ composites amplifies the proinflammatory response, resulting in pyroptotic cell death, setting free functional ASC and inducing a feedforward stimulating vicious cycle. Clustering around ASC fibrils also compromises clearance of Aβ by microglia. Together, these data enable a closer look at the turning point from acute to chronic Aβ-related neuroinflammation through formation of ASC-Aβ composites. : Friker et al. investigate the reaction of primary microglia to exogenous ASC and ASC-Aβ composites. They uncover a vicious circle involving amplified NLRP3 inflammasome activity and reduced Aβ clearance in the presence of ASC that might play a key role in Alzheimer’s disease progression. Keywords: ASC, Aβ, microglia, NLRP3 inflammasome, Alzheimer’s disease